The political ecology of malaria : emerging dynamics of wetland agriculture at the urban fringe in central Uganda - Soest, Matian van, 1984- (Medical humanities (Transcript (Firm)) ;, 2020)
Malaria remains one of the main causes of mortality and morbidity in sub-Saharan Africa. Matian van Soest looks at the malaria epidemic in the peri-urban zones of Uganda's capital Kampala against the backdrop of recent socio-ecological transformations.Based on long-term ethnographic research, the book provides a holistic picture of the malaria epidemic in central Uganda, revealing the highly localized character of an epidemic that once spanned across almost the entire globe. Understanding, and ultimately tackling the disease, requires an appreciation of the social, political, as well as ecological circumstances that frame this epidemic.